Implementasi Peran dan Tugas Komite Sekolah di SMA Negeri Kabupaten Limapuluh Kota - Defawati, Yusra; Hanif, Akhyar; David, David; Munir, Sirajul; Fazis, Muhammad; Asmendri, Asmendri (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Education and learning require collaboration from various aspects, including the involvement of school committees as community representatives in education. The law of education mandates active roles of school committees in improving educational services in schools. However, there are still various problems in implementing the roles and duties of school committees, including constraints in empowerment that still need to be optimally fulfilled in the functions and roles in schools. This research aims to analyze the extent to which the implementation of roles and duties of school committees in Senior High Schools in Limapuluh Kota Regency. The type of research method used is quantitative descriptive with a survey method. This research was conducted at Senior Senior High Schools in Limapuluh Kota Regency, with a sample size of 251 teachers as respondents. Data was collected using a questionnaire instrument while the Aiken and the Construct Validity test using Product Moment Correlation. The reliability test was checked using Alpha Cronbash and the technique of data analysis used descriptive statistical methods, specifically calculating percentages based on the data measured using the Likert scale. Based on the research, data were obtained for the four roles of school committees that can be measured numerically. The school committee has proper roles in fulfilling the responsibility as an advisory agency, a supporting agency, a controlling agency, and a mediator agency. The results of this study indicate that the roles and duties of the school committee in Senior High School in Kabupaten Limapuluh Kota already perform good responsibilities. However, there is still a need for efforts to strengthen and enhance the roles and duties of the school committee in Senior High Schools in Limapuluh Kota Regency.